Bioenergy options for a cleaner environment in developed and developing countries - Sims, Ralph E. H. (Elsevier, 2004)
Bioenergy Options for a Cleaner Environment describes the biomass resource and its delivery. A panel of international experts describe the range of conversion technologies both commercially available and under development, and explore the technical, environmental and socio-economic barriers and benefits of using biomass in both developed and developing countries.*Covers a number of perspectives, taking the reader through the whole process from the bioenergy resource through conversion to fuel, to policy issues.*World class Editor and contributors*Accessible and useful to those
Keywords: Biomass energy : Developing countries; Renewable energy sources : Developing countries